The doctrine of M. ZH. Zhandaev about river valleys (Journal of Geography and Environmental Management, 2016)
Considering the river valley as fluvial geomorphological system, M. Zh. Zhandaev developed a series of new questions about the formation of river valleys in mountain countries. These include theoretical aspects of initial and final stages of the formation of river valleys, meandering channels of the processes of mountain rivers, river interceptions. Justified by the provisions of the transgressive erosion and the relative stability of the watershed. The process of meandering is one of the main channel flow patterns.
Keywords: river; valley; meandering